2023
DOI: 10.1182/bloodadvances.2023011147
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 in patients with classic and variant hairy cell leukemia

Robert J. Kreitman,
Theresa Yu,
Lacey James
et al.

Abstract: Hairy cell leukemia (HCL), like its variant HCLv, is a B-cell malignancy associated with decreased humoral immunity. We prospectively monitored the largest cohort of HCL/HCLv patients to date (n=503) for COVID-19 by symptoms, antibody, PCR and/or antigen-positivity. Fifty percent (253 of 503) of the HCL/HCLv patients (238 HCL, 15 HCLv) had evidence of COVID-19, with 210 (83%) of 253 testing positive by PCR or rapid-antigen. Of 43 without positive tests, all had nucleocapsid antibodies indicating COVID-19 expos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…During the period of health crisis, the mortality rate related to severe acute respiratory syndrome (SARS)-coronavirus-2 (CoV-2) was rather low even among HCL patients with significant immunosuppression and recent treatment. 23 Autoimmune or unusual clinical manifestations are occasionally reported at diagnosis and/or relapse as bulky abdominal lymph nodes, pleural effusions and ascites, skin lesions 24 or destructive bone lesions, some of which can mimic multiple myeloma. [25][26][27] With the high frequency of routine PB analyses, hairy cells can also be detected in asymptomatic patients.…”
Section: How the Diagnosis Of Hcl Has Improved In Daily Practice?mentioning
confidence: 99%
“…During the period of health crisis, the mortality rate related to severe acute respiratory syndrome (SARS)-coronavirus-2 (CoV-2) was rather low even among HCL patients with significant immunosuppression and recent treatment. 23 Autoimmune or unusual clinical manifestations are occasionally reported at diagnosis and/or relapse as bulky abdominal lymph nodes, pleural effusions and ascites, skin lesions 24 or destructive bone lesions, some of which can mimic multiple myeloma. [25][26][27] With the high frequency of routine PB analyses, hairy cells can also be detected in asymptomatic patients.…”
Section: How the Diagnosis Of Hcl Has Improved In Daily Practice?mentioning
confidence: 99%
“…In the same way, in case of pandemic periods such as COVID-19, it is preferable to delay HCL treatment and, if it is not possible, to recommend BRAFi as a bridging therapy [ 129 ]. However, a recently published study on the largest cohort of HCL/HCL-V patients with COVID-19 infection showed a low mortality rate (about 1%) [ 130 ].…”
Section: Treatmentmentioning
confidence: 99%